Quality Evaluation Methods of Development Process of Complex Electromechanical Device - Yang Liangen; Zheng Lin (Institute of Advanced Engineering and Science, 2012)
This paper describes the design of the overall structure about evaluation system of the development process of complex electromechanical device, and analyzes quality evaluation of the stage of scheme design in detail. An evaluation index system of quality of development process is proposed based on resources and conditions, technical status control, management control. Take the evaluation of scheme design stage of ship development as an example, evaluation index system at that stage is established and optimized. DOI:http://dx.doi.org/10.11591/telkomnika.v10i6.1412